Investigation of drying apple snack convection-termoradiatsiynym energy to wrap different power heaters - Malezhik, Ivan; Strelchenko, Ljudmila; Dubkovetskyy, Igor (My University, 2016)
During drying apple snacks to obtain high-quality product should choose optimum parameters of drying and rational use of energy, materials and time. The intensity of the thermal radiation-convection drying largely depends on the capacity of heaters, used for the process. The purpose of the given research is to determine the optimal load heaters. Під час сушіння яблучних снеків для отримання високоякісного продукту слід вибирати оптимальні параметри сушіння та раціональне використання енергії, матеріалів і часу. Інтенсивність сушіння теплового випромінювання-конвекції багато в чому залежить від потужності нагрівачів, що використовуються для процесу. Метою даного дослідження є визначення оптимального навантажувального нагрівача.
Keywords: thermal radiation-convective drying; product range; moisture content; the intensification of the drying process; the load heaters; snack; теплова радіаційно-конвективна сушка; асортимент; вологість; інтенсифікація процесу сушіння; нагрівачі нагріву; закуски; кафедра процесів і апаратів харчових виробництв